PELATIHAN KADER POSYANDU SEBAGAI UPAYA PENCEGAHAN STUNTING PADA BALITA DI WILAYAH KERJA PUSKESMAS MARGADANA DAN PUSKESMAS TEGAL SELATAN KOTA TEGAL - Heni Purnamasari; Zahroh Shaluhiyah; Aditya Kusumawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Stunting is a global and Indonesian problem due to inadequate nutritional needs of children during the First 1000 Days of Life (HPK). This research aims to analyze the effect of cadre training on stunting prevention in toddler. This type of research is Quasy-Experimental with unequal control group design. The research sample consisted of 64 posyandu cadres taken using purposive techniques according to inclusion criteria. The training used counseling methods, giving a stunting cadre guidebook, and two weeks of field practice. The result of Wilcoxon test analysis in the experimental group after the training gives differences in knowledge (p=0,000), self-efficacy (p=0.002), and practice (p=0,000). While attitudes do not produce a difference (p=0.182). Although there was no change in attitude, it happened because posyandu cadres showed a positive attitude about stunting before the training was conducted. An increase in knowledge, attitudes, self-efficacy, and practice after the intervention shows that the stimulus can be received effectively, so that it influences attention, then there is a willingness to act, and forming beliefs in individuals that have an impact on actualizing actions or changing behavior. In the control group there were no differences in knowledge, attitudes, self-efficacy, and practices in the pre-test and post-test (p>0.05). The Mann Whitney test in the both groups produced differences in knowledge and practice with values (p=0,000). It can be concluded that the training of stunting cadres using the stunting cadre guidebook along with field practice assistance is quite effective in increasing knowledge, self-efficacy, and practices of posyandu cadres in efforts to prevent stunting cases in toddler. Good respondent's self-efficacy needs to be maintained and improved to produce good performance. This research suggests that posyandu cadres can do their duties according to the five main service packages for stunting prevention so that the number of stunting in toddler can be reduced.